Improving Critical Thinking Skills of Prospective Biology Teacher Students through Ethnoscience-Based Biology Learning - Haryanto, Toni; Kencanawati, Indah (Tarbawi : Jurnal Ilmu Pendidikan, 2023)
Ethnoscience is one of the activities in transforming indigenous science into scientific science that can be implemented in the biology learning process. The implementation of the ethnoscience stage in biology learning perhaps can improve students' critical thinking skills, which is the aim of this research. This research is experimental research using a pretest-posttest control group design. The research population consisted of 36 students. The sample selection used a random sampling technique consisting of 2 classes (experimental and control), each class consisting of 18 students. Research data was obtained through pretest and posttest. There are 10 questions with 5 indicators of critical thinking skills through a minimal structure essay test. The results of the research show that there is an increase in students' critical thinking skills in understanding concepts that integrate native community knowledge into scientific knowledge through the ethnoscience stage compared to critical thinking skills that do not go through ethnoscience-based learning in biology learning. Therefore, ethnoscience-based learning is recommended to be applied in the learning process in other subjects such as biotechnology and bioappliance to help improve critical thinking skills and other skills in simplifying content-rich biological material.